2018
DOI: 10.1126/sciadv.aan8917
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced dynamic structural color by intracellular 3D photonic crystals in brown algae

Abstract: A photosynthetic algal intracellular organelle containing a living opal responds dynamically to environmental illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…It can conveniently transfer the complex patterns from soft copies into hard copies by light irradiation 38,39. However, to achieve the artificial light‐induced tunable structural color like the brown algae in nature is not easy 40. On one hand, one pattern with multiple structural colors is hard to realize because it is difficult to apply different stimuli to adjacent microregions.…”
Section: Methodsmentioning
confidence: 99%
“…It can conveniently transfer the complex patterns from soft copies into hard copies by light irradiation 38,39. However, to achieve the artificial light‐induced tunable structural color like the brown algae in nature is not easy 40. On one hand, one pattern with multiple structural colors is hard to realize because it is difficult to apply different stimuli to adjacent microregions.…”
Section: Methodsmentioning
confidence: 99%
“…Much comes from inherently coloured molecules that absorb light (i.e., chlorophyll) or compounds that luminesce (i.e., luciferin). However, a myriad of deep structural colours (iridescence) in the marine environment come from the nanostructuration of the material and has evolved independently across many phyla [228], including crustaceans [229][230][231], fish [232][233][234][235], bivalves [236,237], cephalopods [238], algae [239][240][241][242], diatoms [243], bacteria [244], etc. In the animal world, this type of colouration has been linked to camouflage, predation, signal communication and sex choice [245].…”
Section: Structural Colouration In the Marine Environmentmentioning
confidence: 99%
“…It has been suggested that some plants and macro‐algae use photonic structures to support their light harvesting and photosynthesis. [ 6,7 ] Earlier studies also discussed the possible role of the frustule related to its light modulating properties for photosynthesis, mainly by facilitated passage for photosynthetically more productive, or attenuation of potentially harmful radiation. [ 18,32 ] As both sPhC properties (pseudogap and guided modes) resonate in the range where light absorption for photosynthesis in diatoms is low, [ 33 ] we speculate that the C. granii girdle sPhC is not tuned for manipulation of photosynthetically more productive wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were characterized on an advanced Fourier image spectroscopy in a microscope setup adapted for the study of natural photonic systems. [ 7 ] Initially, glass cover slips were prepared with poly‐L‐lysine solution (P4707, Sigma Aldrich, St. Louis, USA). By this, frustule pieces were fixed onto the glass and did not move during immersion measurements with water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation